Pyrinex 48 EC és Chorus 50 WG peszticidek együttes embriókárosító hatásának vizsgálata fácánembrión - Major, László; Budai, Péter; Buda, István; Saidon, Nadhirah Binti; Lehel, József; Szabó, Rita (GEORGIKON FOR AGRICULTURE, 2023)
The aim of this study was to determine the individual and combined toxic effects of Pyrinex 48 EC insecticide (480 g/l chlorpyriphos) and Chorus 50 WG fungicide (500 g/kg cyprodinil) on the development of pheasant embryos. Emulsion and suspension of the test materials were injected in 0.1 ml volume into the air chamber of the pheasant eggs before starting the incubation. The pheasant embryos were examined on day 21 by the followings: body weight, rate of embryo mortality, rate and type of developmental anomalies by macroscopic examination. With the exception of the fungicide-treated group, the average body weight of the pheasant embryos in the treated groups was significantly lower than that of the control group. The single and simultaneous administration of the Pyrinex 48 EC increased the mortality of pheasant embryos significantly and developmental anomalies as compared to the control. There was presumably additive type toxic interaction between Pyrinex 48 EC and Chorus 50 WG. The test materials were embryotoxic in pheasant.
Keywords: chlorpyriphos; cyprodinil; pheasant embryo; interaction; ecotoxicology